Do Global Trade Distortions Still Harm Developing Country Farmers? - Anderson, Kym (World Bank, Washington, DC, 2012)
The authors estimate the impact of global merchandise trade distortions and services regulations on agricultural value added in various countries. Using the latest versions of the Global Trade Analysis Project (GTAP) database and the GTAP-AGR model of the global economy, their results suggest real net farm incomes would rise in developing countries with a move to free trade, thereby alleviating rural poverty. This occurs despite a terms of trade deterioration for developing countries that are net food importers or that enjoy preferential access to agricultural markets of high-income countries. The authors also show, for several large developing countries, the contribution of their own versus other countries' trade policies.